Research on“Wo Connect”Uniform Authentication Technology - Di Liu; Yunyong Zhang; Ni Zhang; Manjun Zhang (Dianxin kexue)
Recently，many web user data leak incidents outbreak. In order to protect web user personal information，an analysis was made on security threats for web user，emphasizing security requirements. And a web-based strong authentication scheme，“Wo Connect”uniform authentication solution，was proposed. Based on user mobile phone number identifier，this solution provides the third party website uniform security authentication ability，enabling user to enjoy security and convenience authentication and authorization user experience.